Managing SARS-CoV2 Infections Through Resolution of Inflammation by Eicosanoids: A Review - Mohammed A; Kalle AM; Reddanna P (Journal of Inflammation Research, 2022)
Ameena Mohammed,1 Arunasree M Kalle,2 Pallu Reddanna2 1Department of Biological Science, Indian Institute of Science Education and Research Kolkata, Nadia, West Bengal, 741246, India; 2Department of Animal Biology, School of Life Sciences, University of Hyderabad, Hyderabad, 500046, IndiaCorrespondence: Pallu Reddanna; Arunasree M Kalle, Department of Animal Biology, School of Life Sciences, University of Hyderabad, Hyderabad, TS, 500046, India, Tel +91 4023134542, Fax +91 4023134120, Email prsl@uohyd.ac.in; arunasreemk@uohyd.ac.inAbstract: Severe Corona Virus Disease is characterized by angiocentric inflammation of lungs and cytokine storm leading to potentially fatal multiple organ failure. Several studies have shown the high levels of pro-inflammatory cytokines, indicative of a poor prognosis in COVID-19. Eicosanoids play an important role in the induction of inflammation and cytokine production, while anti-inflammatory and pro-resolving properties of some eicosanoic acid derivatives enable inflamed tissues to return to homeostasis through the resolution of inflammation by aiding the clearance of cell debris and downregulation of pro-inflammatory stimulants. This review attempts to provide an overall insight on the eicosanoids synthesis and their role in the resolution of inflammation in the context of Corona Virus infection.Keywords: COVID-19, lipid mediators of inflammation, polyunsaturated fatty acids, cyclooxygenases, lipoxygenases, cytochrome P450, eicosanoids